Game-Changing Antibiotic Solutions for Chronic UTIs in Women - Makowska, Karolina; Billewicz, Marta; Perwejnis, Sebastian; Marczyk, Aleksandra (Quality in Sport, 2024)
Urinary tract infections (UTIs) are prevalent in primary healthcare settings, with persistent recurrences posing significant challenges. These recurrences necessitate extended antibiotic use, adversely affecting patients' quality of life, mental health, and physical activity. The evolving defense mechanisms of bacteria against the host immune system and antibiotics complicate treatment. This article examines the pathomechanisms of recurrent UTIs, focusing on bacterial defense factors. Understanding these mechanisms is essential for developing innovative treatments, particularly non-antibiotic methods, to reduce antibiotic use and its associated side effects, thereby improving patients' overall well-being. The review synthesizes current knowledge on the pathomechanisms, diagnostics, and treatments for recurrent UTIs, emphasizing the impact on patients' mental and physical health. It highlights innovative, non-antibiotic treatment approaches.